Assessing Student Performance Designing Props and Experiments Physics In Learning Team Base Project For Subject Instrumentation - I Komang Werdhiana; Haeruddin; Muhammad Jarnawi; Syamsuriwal (Postgraduate, University of Mataram, 2025)
Performance assessment is an important part of learning that applies the team-based project method. This study aims to describe student performance in designing physics teaching aids and experiments in terms of active participation, understanding of the material, presentation skills and products. This study uses a descriptive method. Data were obtained through observation sheets and rubrics and assessment sheets. Data analysis for active participation, understanding of the material, and presentation skills was carried out by determining the number of students who obtained scores according to each category (very good, good, quite good, and less good) then expressed as a percentage. Data analysis for product assessment was carried out by determining the average score of each product and converting it to a score of 100. There were 29 students who were the sample of the study. The results of the study showed that students who participated actively were predominantly in the sufficient and less active categories. The percentage of students who understood the material was predominantly in the understand and understand enough categories. Students' presentation skills were predominantly in the good category. All the results of the teaching aid designs were in the very good category. There were three experimental design results in the very good category and three others in the good category. Based on the research results, it can be concluded that students are able to design physics demonstration tools and experiments in terms of active participation, understanding of the material, presentation and product skills, through team-based project learning.